APLIKASI BOOKING KOST BERBASIS ANDROID DI KOTA PALANGKA RAYA - Enny Dwi Oktaviyani; Deddy Ronaldo; Mustafa Arifin (JURNAL TEKNOLOGI INFORMASI, 2019)
The development of information technology and computers is currently very rapid, especially in the field of communication technology, namely smartphones. While the operating system is currently very well known by the public, namely the Android operating system. The city of Palangka Raya is one of the places of education that is the destination of prospective students from various regions. Then they have to find a place to stay while the study is finished and this process will waste a lot of time. So from that we need a facility or media to facilitate the search process of kos by utilizing smartphone technology and the Android operating system. The method used to design and build this application is the waterfall method. The design process is using flowcharts, use case diagrams, activity diagrams, class diagrams, database design and user interface design. Supporting applications are Sublime Text, Android Studio, XAMPP, MySQLyog and blackbox testing